Detection of the KIAA1549-BRAF fusion gene in cells forming microvascular proliferations in pilocytic astrocytoma. - Shinji Yamashita; Hideo Takeshima; Fumitaka Matsumoto; Kouji Yamasaki; Tsuyoshi Fukushima; Hideyuki Sakoda; Masamitsu Nakazato; Kiyotaka Saito; Asako Mizuguchi; Takashi Watanabe; Hajime Ohta; Kiyotaka Yokogami (PLoS ONE, 2019)
Microvascular proliferation (MVP), an aberrant vascular structure containing multilayered mitotically active endothelial- and smooth-muscle cells/pericytes, is a histopathological hallmark of glioblastoma multiforme (GBM). Although MVP tends to be associated with high-grade glioma, it has also been detected in WHO grade I pilocytic astrocytoma (PA). However, little is known about the mechanism underlying its formation. Using TP53 point mutations as a marker for tumor-derived cells, we earlier reported that MVP was partially converted from tumor cells via mesenchymal transition. In the current study we used the KIAA1549-BRAF fusion gene as a marker to assess whether MVPs in PA contained tumor-derived cells and/or phenotypically distinct tumor cells expressing vascular markers. cDNA synthesized from frozen tissue of six PA patients operated at our institute was analyzed to detect the KIAA1549-BRAF fusion gene by reverse transcription polymerase chain reaction (RT-PCR) assay. The breakpoint in the fusion gene was identified by long and accurate PCR (LA-PCR) and Sanger sequencing of genomic DNA. Distinct tumor cells and cellular components of MVP were obtained by laser microdissection. For the qualitative and quantitative detection of the KIAA1549-BRAF fusion gene we performed genomic and digital PCR assays. Fluorescence in situ hybridization (FISH) was used to assess gene fusion in cellular components of MVP. Samples from three PA patients harbored the KIAA1549 exon 15, BRAF exon 9 fusion gene. In two patient samples with abundant MVP, RT-PCR assay detected strong bands arising from the KIAA1549-BRAF fusion gene in both tumor cells and cellular components of MVP. Digital PCR showed that vis-à-vis tumor tissue, its relative expression in cellular components of MVP was 42% in one- and 76% in another sample. FISH revealed amplified signals in both tumor cells and cellular components of MVP indicative of tandem duplication. Our findings suggest that in patients with PA, some cellular components of MVP contained tumor derived cell and/or phenotypically distinct tumor cells expressing vascular markers.